(untitled) - Leavitt, Teddy C. (New York, 1967)
This text is a study of limits and continuity, and is designed to supplement standard calculus text. It discusses limits and continuity in several different ways, since students gain understanding through comparison.
Keywords: Continuity,Liên tục